Hadis-hadis dalam Kitab Durrat al-Nāṣiḥīn - Ahmad Lutfi Fathullah (Refleksi: Jurnal Kajian Agama dan Filsafat, 2008)
One of the traditions in the Muslim community is reading or studying the Kitab Kuning (classical Islamic texts). There are quite a variety of Kitab Kuning that are read in pesantren (Islamic boarding schools) or study groups, one of which is the book Durrat al-Nāṣiḥīn. This text is a summary of the author’s dissertation at Universiti Kebangsaan Malaysia (UKM) titled A Study of Hadith in the Book Durrat al-Nāṣiḥīn.